Genetic risk factors for cancer-related cognitive impairment: a systematic review. (4th May 2019) - Buskbjerg, Cecilie D. R.; Amidi, Ali; Demontis, Ditte; Nissen, Eva R.; Zachariae, Robert
Abstract: Background: Cancer-related cognitive impairment (CRCI) is a commonly reported complaint among non-CNS cancer patients. Even subtle CRCI may have detrimental effects on quality of life and identifying patients at increased risk for CRCI to improve survivorship care is important. In the present paper, we systematically reviewed available studies of possible genetic risk factors for developing CRCI. Methods: Keyword-based systematic searches were undertaken on 24 July 2018 in PubMed, Web of Science, The Cochrane Library, and CINAHL. Three authors independently evaluated full-texts of identified papers and excluded studies with registration of reasons. Seventeen studies reporting results from 14 independent samples were included for review. Two authors independently quality assessed the included studies. The review was preregistered with PROSPERO (CRD42018107689). Results: Ten studies investigated apolipoprotein E (APOE), with four studies reporting that carrying at least one risk allele (APOE4 (ε4)) was associated with CRCI, while six studies found no association. The remaining identified genetic risk variants associated with CRCI located in: COMT, four DNA repair genes, five oxidative stress genes, 22 genes related to breast cancer phenotype, and GNB3 . No associations were found between CRCI and genes coding for interleukin-6 ( IL6 ), tumor necrosis factor alpha ( TNF ), interleukin 1 beta ( IL1B ), and brain-derived neurotropic factor ( BDNF ). With the exception of APOE, the genetic risk factors had only been investigated in one or two studies each. Conclusions: Overall, the available evidence of possible genetic risk factors for CRCI is limited. While some research suggests a role for the ε4 allele, the literature is generally inconsistent, and the currently available evidence does not allow clear-cut conclusions regarding the role of genetic factors in the development of CRCI. Larger genetic studies and studies investigating additional genetic variants are needed to uncover genetic risk factors for CRCI.